The Effects Of Organizational Efforts On Productivity Performance In The Government Service In Penang Moderated By The Service Characteristics - RAMLI, ROSIDAH (2005)
The study sought to determine the effects of organizational efforts on productivity performance and to investigate whether service characteristic moderates the relationship between these organizational efforts and productivity performance. Basically, the study was done in government service department in Penang as Malaysia is now in the era of globalization.